Regional Innovation Ecosystems: Tuning the Regional Engine’s Helix Through Smart Specialization - Lopes, João (2021)
The present research aims to contribute for the analysis of the theoretical evolution of the triple helix, quadruple helix, quintuple helix and multiple helix concepts, embracing the dynamic interaction of different stakeholders in the context of regional innovation systems. Following a preliminary literature review on the subject, it was possible to develop a systematic literature review with a bibliometric analysis of research that addressed the evolution of the triple helix until the multiple helix, into the regional innovation systems perspective. Extensive research was conducted using the Web of Science database between 1990-2018, covering a total of 378 articles, generators of 9991 citations. Four clusters were found in the literature for this field of research: R&D Collaborations and Innovation; Entrepreneurial Activity in Entrepreneurial University; Triple Helix Dynamics, and Quadruple Helix in Regional Innovation Systems. New theoretical perspectives based on bibliometric analysis and new research paths have been identified, aiming to better understand the regional interaction of stakeholders for innovation and entrepreneurship.